Estimation of in vivo inter-vertebral loading during motion using fluoroscopic and magnetic resonance image informed finite element models. (21st March 2018) - Zanjani-Pour, Sahand; Meakin, Judith R.; Breen, Alex; Breen, Alan
Abstract: Finite element (FE) models driven by medical image data can be used to estimate subject-specific spinal biomechanics. This study aimed to combine magnetic resonance (MR) imaging and quantitative fluoroscopy (QF) in subject-specific FE models of upright standing, flexion and extension. Supine MR images of the lumbar spine were acquired from healthy participants using a 0.5 T MR scanner. Nine 3D quasi-static linear FE models of L3 to L5 were created with an elastic nucleus and orthotropic annulus. QF data was acquired from the same participants who performed trunk flexion to 60° and trunk extension to 20°. The displacements and rotations of the vertebrae were calculated and applied to the FE model. Stresses were averaged across the nucleus region and transformed to the disc co-ordinate system (S1 = mediolateral, S2 = anteroposterior, S3 = axial). In upright standing S3 was predicted to be −0.7 ± 0.6 MPa (L3L4) and −0.6 ± 0.5 MPa (L4L5). S3 increased to −2.0 ± 1.3 MPa (L3L4) and −1.2 ± 0.6 MPa (L4L5) in full flexion and to −1.1 ± 0.8 MPa (L3L4) and −0.7 ± 0.5 MPa (L4L5) in full extension. S1 and S2 followed similar patterns; shear was small apart from S23. Disc stresses correlated to disc orientation and wedging. The results demonstrate that MR and QF data can be combined in a participant-specific FE model to investigate spinal biomechanics in vivo and that predicted stresses are within ranges reported in the literature.